2013
DOI: 10.2478/bpasts-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

The digital function filters – algorithms and applications

Abstract: The simple digital filters are not sufficient for digital modeling of systems with distributed parameters. It is necessary to apply more complex digital filters. In this work, a set of filters, called the digital function filters, is proposed. It consists of digital filters, which are obtained from causal and stable filters through some function transformation. In this paper, for several basic functions: exponential, logarithm, square root and the real power of input filter, the recursive algorithms of the dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This publication presents the mathematical convolution method as well as digital filter impulse response method with the application for distributed parameters system analysis in the theory of electrical circuits. The authors' previous studies in this field can be found in publications [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This publication presents the mathematical convolution method as well as digital filter impulse response method with the application for distributed parameters system analysis in the theory of electrical circuits. The authors' previous studies in this field can be found in publications [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Often it is better to use a recursive method, which is more effective for some function f(A). More about the functional filters can be found in [6]. In this paper two important functional filters are used: f A A ( )= …”
Section: Functional Filtersmentioning
confidence: 99%
“…Such a multistage speech processing for the speaker recognition is composed of: a parameterization of the input signal (preprocessing e.g. with the use of digital function filters [11], signal division into blocks, multiplication by a window function, determining the linear prediction coefficients or mel-cepstral coefficients with the use of the FFT), a modeling phase (such as the vector quantization and the creation of mixtures of Gaussians) and then comparing with the base pattern [2].…”
Section: Introductionmentioning
confidence: 99%